Identification and correction of phase delay errors for hemispherical resonator gyroscopes - Youhuan Ning; Changhong Wang; Boqi Xi; Zhen Tian; Boda Zhang (Scientific Reports)
Abstract The phase-delay error of the circuit system is the primary source of the output error observed in the hemispherical resonator gyroscope (HRG). Additionally, the temperature-dependent nature of the phase-delay error results in a deterioration of the initial calibration parameters, which, in turn, significantly impairs the performance of the gyroscope in its intended application. This paper proposes a self-calibration method to effectively suppress the impact of phase-delay error on the application performance of gyroscopes. Firstly, based on the analysis of the influence of phase-delay error on the performance of the whole-angle mode HRG, a sinusoidal interference signal with a small amplitude is introduced into the quadrature control loop of the gyroscope. Then, the angular rate signal is demodulated and calculated to obtain the phase-delay error of the system, which is employed as the compensation value of the reference phase of the PLL to offset the phase-delay error of the circuit system in real-time. The experimental results demonstrate that after the phase-delay error is self-calibrated, the zero-bias output error of the gyroscope is reduced by 5 times, the bias instability is improved by 37.7%, and the self-calibration method of the phase-delay error presented is more strongly robust to temperature changes.